PENGARUH SUBSTITUSI RUMPUT LAUT (Eucheuma cottonii) DALAM PAKAN RUMPUT GAJAH (Pennisetum purpureum) TERHADAP KONSENTRASI VFA PARSIAL DAN ESTIMASI PRODUKSI GAS METANA SECARA IN-VITRO - Denis Hikmawan, Erwanto, Muhtarudin, dan Farida Fathul (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2019)
The objective of this study was to determine effect of Eucheuma cottonii seaweed substitution in elephant grass on in vitro individual VFA and methane gas production estimation. This in vitro research was conducted in Laboratory of Nutrition of Indonesia Livestock Research Institute (ILRI), Ciawi, Bogor from October to November 2018. This research used Completely Randomized Design with 4 treatments and 3 replications. The treatments wereP0 = Elephant Grass 100%; P1 = Elephant Grass 96% + E. cottonii 4%; P2 = Elephant Grass 92% + E. cottonii 8%; dan P3 = Elephant Grass 88% + E. cottonii 12%.The data obtained were analyzed using covariance and continued with the Least Significance Difference (LSD) test. The results showed that Eucheuma cottonii seaweed substitution level in elephant grass has highly significant effect (P<0,01) on total VFA, acetate, propionate, butyrate acid proportion and methane gas production estimation. Moreover, there is the best level of Eucheuma cottonii seaweed in decreasing methane gas production estimation on 4% level with producing 18,49 mM of methane gas although total VFA (58,05mM) and individual VFA are also decreasing both of acetate acid 38,02 mM, propionate acid 11,33 mM, and butyrate acid 4,61 mM. Keywords :Volatile fatty acid (VFA), Methane gas, Seaweed, Elephant grass, In vitro